Madrasa Education System in Bihar - Pandey, Lakshmi (JOURNAL OF INDIAN EDUCATION, 2019)
Madrasas have become a symbol of Muslim identity in India. They are an indispensable component of the minority community, tasked with imparting the knowledge of Islam to the younger generation. This paper aims to assess the infrastructure facilities available in madrasas accounting for teachinglearning processes in Bihar. A Multistage Sampling Design (MSD) with different stratifying parameters was adopted for the selection of sample units at different levels. The present study was administered on a sample of 220 students and 22 principals from 22 madrasas in a district of Bihar. In order to map out the objectives of the study, two data capture formats (DCF) namely—Madrasa Management Schedule and Student Schedule were prepared and used for the study. The results show a lack of contemporary educational resources, such as proper school building, classrooms, furniture and blackboard, in some of the madrasas. Moreover, the quality of teachers was found to be unsatisfactory; they had never received proper training either from a government organisation or the Waqf Board. It is, hence, safe to conclude that the madrasas are not at par with government schools.